Human Reliability Assessment dengan Metode Human Error Assessment and Reduction Technique pada Operator Stasiun Shroud PT. X - Dian Mardi Safitri; Ayu Rachma Astriaty; Nataya C. Rizani (Jurnal Rekayasa Sistem Industri, 2015)
Human realibility is a big tricky problem. Human failure rates depend on three main factors, namelyintrinsic, work environment, and stress. PT. X is a supplier for PT. LG Indonesia manufacturing productsmade from plastics. Human Realibility Assesment is conducted using HEART methods (Human ErrorAssessment and Reduction Technique). In the first phase, task analysis on operators’ activities is done usingHierarchical Task Analysis (HTA). The largest Human Error Probability was found when Operator No. 1did not insert the flash side carefully. The value of this probability is 0.53424. This factor is concluded as themain cause to shroud defectives, which results in customer penalyzing the company.